2x+3y=59

Simple and best practice solution for 2x+3y=59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3y=59 equation:


Simplifying
2x + 3y = 59

Solving
2x + 3y = 59

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3y' to each side of the equation.
2x + 3y + -3y = 59 + -3y

Combine like terms: 3y + -3y = 0
2x + 0 = 59 + -3y
2x = 59 + -3y

Divide each side by '2'.
x = 29.5 + -1.5y

Simplifying
x = 29.5 + -1.5y

See similar equations:

| 36=4x-12 | | -5+2k=5 | | 7x=7+x | | 12x^3-8x^2-4x-35=0 | | 11t(4-t)=2(5-3t) | | sqrt(x+2*sqrt(x-1))-sqrt(x-2*sqrt(x-1))=2 | | 6x+7=100+3x-20 | | 6x+7=1003x-20 | | 36x^2-476x-2462=0 | | x^2+5x-10=14 | | -8x-34=9x | | 2y-36=5y-2y | | 2(26+-2y+-3z)+3y+z=34 | | 3(26-2y-3z)+3y+z=34 | | 3(26-2y-3z)+2y+z=39 | | X-2y+9z=6 | | -9x+11=2x | | 15X^4-(30X^2)+7=0 | | 4m+5=27 | | 4(c+10)-146=6 | | x=26+-2y+-3z | | 11x-11=4x+9 | | 3(4-3x)=9(5-2x) | | 2w+2.9=13.5 | | 5x+12-(2x-12)=-3x+9 | | 15X^4-(30X^2)(L^2)+7=0 | | 17x+14y=930 | | 12x+53=9x+15+x | | 9x+3=-53+2x | | x+48=-5x | | 3x-0.79=1.2+2x | | Cotx=3.45 |

Equations solver categories